Clinical outcome of patients with orbital fractures treated with patient specific CAD/CAM ceramic implants – A retrospective study. Issue 6 (June 2021) - Falkhausen, Runa; Mitsimponas, Konstantinos; Adler, Werner; Brand, Michael; von Wilmowsky, Cornelius
Abstract: The aim of this study was to determine whether patients benefit from a secondary reconstruction since it carries the risks of no improvement or worsening of their current situation. Patients treated with individual computer-aided-design/computer-aided-manufacturing (CAD/CAM) ceramic implants were reviewed. To ascertain changes throughout the secondary reconstruction, the study investigators reviewed ophthalmological examinations, took volumetric measurements of the orbits and asked the patients for evaluation of their situation before and after the reconstruction. Points addressed were double vision, visual acuity, field of vision, limitations in daily life and aesthetic considerations. A total of 14 patients were reviewed and 11 answered the questionnaire. Ophthalmological examinations showed that the physical integrity of the eye was maintained. Volumetric measurements preopeatively (33.94 ± 3.24 cm 3 ) and postoperatively (30.67 ± 2.07 cm 3 ) showed that a statistically significant overcorrection of orbital volume leads to good functional and aesthetic outcomes. Patients' subjective opinions were that they greatly benefitted, especially concerning limitations in daily life, which improved by 4.4 ± 2.8 points out of 10 possible points, and aesthetics, with an improvement of 5.9 ± 1.78 points. Based on these findings, we conclude that secondary reconstructions contribute to improvement of the patients' quality of life and therefore should be considered as an option to improve patients' condition.